Exporting firm dynamics and productivity growth: Evidence from China - Huang Xiaobing; Liu Xiaolian (Kiel Institute for the World Economy (IfW), 2015)
This paper analyzes the reallocation effects generated by dynamics of exporting firms adopting DOPD productivity decomposition. The authors select the exporting firm samples from the dataset of Annual Surveys of Industrial Production for the period from 2005 to 2009. The study indicates that the surviving ability of exporters is weak, and that firm turnover is turbulent. The reallocation effects generated by firm dynamics contributes almost half of productivity improvement. It mainly originates from between-firm effects, rather than firm turnover effects, with the entry effects being negative. This suggests that there is market misallocation, which maybe caused by uneven regional development, industrial monopoly or state-owned enterprises.
Keywords: F14; D40; D22; D24; 330; exporting firms; firm dynamics; productivity growth; reallocation effect; China